2008
DOI: 10.1593/neo.07871
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity in Tumor-Promoting Inflammation: Impairment of Macrophage Recruitment Evokes a Compensatory Neutrophil Response

Abstract: Previous studies in the K14-HPV/E(2) mouse model of cervical carcinogenesis demonstrated that infiltrating macrophages are the major source of matrix metalloproteinase 9 (MMP-9), a metalloprotease important for tumor angiogenesis and progression. We observed increased expression of the macrophage chemoattractant, CCL2, and its receptor, CCR2, concomitant with macrophage influx and MMP-9 expression. To study the role of CCL2-CCR2 signaling in cervical tumorigenesis, we generated CCR2-deficient K14-HPV/E(2) mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
156
3
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 192 publications
(175 citation statements)
references
References 36 publications
11
156
3
5
Order By: Relevance
“…Data from a genetically engineered skin cancer model and transplantable mammary tumor models indicate that neutrophil infiltration into tumors and their systemic expansion is increased following macrophage blockade via CSF1R or CCR2 signaling 200,201 . Given the tight interplay between neutrophils and macrophages 131 , neutrophils may be expected to promote resistance to macrophage-targeting therapies.…”
Section: Combining Neutrophil Targeting With Other Anti-cancer Therapiesmentioning
confidence: 99%
“…Data from a genetically engineered skin cancer model and transplantable mammary tumor models indicate that neutrophil infiltration into tumors and their systemic expansion is increased following macrophage blockade via CSF1R or CCR2 signaling 200,201 . Given the tight interplay between neutrophils and macrophages 131 , neutrophils may be expected to promote resistance to macrophage-targeting therapies.…”
Section: Combining Neutrophil Targeting With Other Anti-cancer Therapiesmentioning
confidence: 99%
“…The increase in neutrophils and circulating Ly6C hi monocytes following CSF-1R (AFS-98) or CSF-1 neutralization in 4T1.2 and EMT6.5 tumors was unexpected, although compensatory increases in neutrophils have been reported in infections of macrophage-deficient Csf1 op /Csf1 op mice (54), and after reduction of macrophages in a murine cervical cancer model (55). Using a similar protocol in non-tumor-bearing mice in the steady state or during inflammation, we and others found that AFS-98 antibody has no effect on these cell populations (35,56).…”
Section: Neutrophils Macrophagesmentioning
confidence: 99%
“…If TAM accumulation is suppressed, neutrophils are recruited to the tumor providing a secondary source of MMP-9. Therefore, in the absence of TAMs, TANs provide alternative paracrine support for tumor angiogenesis and progression [171]. Hence, the elimination of TAMs alone may be insufficient to eradicate myeloid cell support to tumor growth.…”
Section: Therapeutic Approaches Targeting Tamcsmentioning
confidence: 99%